1996
DOI: 10.1002/(sici)1096-8628(19960329)62:3<216::aid-ajmg3>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

FISH detection of chromosome 15 deletions in Prader-Willi and Angelman syndromes

Abstract: We have evaluated fluorescence in situ hybridization (FISH) analysis for the clinical laboratory detection of the 15q11‐q13 deletion seen in Prader‐Willi syndrome (PWS) and Angelman syndrome (AS) using probes for loci D15S11, SNRPN, D15S10, and GABRB3. In a series of 118 samples from patients referred for PWS or AS, 29 had deletions by FISH analysis. These included two brothers with a paternally transmitted deletion detectable with the probe for SNRPN only. G‐banding analysis was less sensitive for deletion de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Subsequent studies have demonstrated submicroscopic deletions in some of these kindreds [Saitoh et al, 1997]. The submicroscopic deletion was also present in the sibs' father in two cases [Buiting et al, 1995; Teshima et al, 1996]. In another instance, the father was not available for testing, but the deletion was present in the paternal grandmother [Reis et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies have demonstrated submicroscopic deletions in some of these kindreds [Saitoh et al, 1997]. The submicroscopic deletion was also present in the sibs' father in two cases [Buiting et al, 1995; Teshima et al, 1996]. In another instance, the father was not available for testing, but the deletion was present in the paternal grandmother [Reis et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these recurrences were due to inheritance of an unbalanced translocation from a carrier father [Fernandez et al, 1987; Hasegawa et al, 1984; Hultén et al, 1991]. Several families have been reported in which sibs and their normal father all have submicroscopic deletions of 15q11–q13 that likely involve the imprinting center [Buiting et al, 1995; Ishikawa et al 1996; Orstavik et al, 1992; Reis et al, 1994; Teshima et al, 1996]. We provide the first report of cousins with Prader‐Willi syndrome with cytogenetically normal chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…In retrospect, some of the apparently atypical features of PWS-29, such as the less-typical facies, may be ascribed to the clinical differences found in African American patients with PWS (Hudgins et al 1998). Whereas one of the affected PWS-T sibs had most of the clinical diagnostic features of PWS, his younger brother, at age 7 years, only had infantile hypotonia, language delay, and above-average weight, without hyperphagia (Teshima et al 1996). Patients PWS-B ( fig.…”
Section: Clinical Analysis Of Patients With An Immentioning
confidence: 99%
“…Brief reports for patients with novel molecular findings are presented here, for comparison with typical patients with a PWS deletion and UPD, who display neonatal hypotonia with a failure to thrive, hyperphagia and severe obesity, mental retardation with learning disabilities, obsessive-compulsive disorder, hypogonadism, short stature, and small hands and feet (Cassidy 1997). Clinical and cytogenetic studies of two affected sibs in each of the families PWS-J and PWS-T have been reported elsewhere (Ishikawa et al 1996;Teshima et al 1996).…”
Section: Clinical Reportsmentioning
confidence: 99%
“…The incidence is 1 in 10 000-15 000 (2) and the majority of cases are sporadic. A small number of families have been reported with two or more affected siblings (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%